Permeability Barrier to Rifampin in Mycobacteria - Hui, J. (1977)
A strain of Mycobacterium intracellulare that exhibited natural resistance to rifampin was isolated. The ribonucleic acid polymerase was found to be susceptible to rifampin. Studies with Tween 80 suggested that a permeability barrier against rifampin was present in the intact organism. A type strain of Mycobacterium smegmatis, ATCC 607, considered resistant to rifampin also demonstrated a permeability barrier. The possibility that rifampin resistance in naturally occurring strains of mycobacteria and variable levels of resistance in strains of certain species of this organism are due to permeability barriers is discussed.